Constructing Islamic Moderation in Arabic Digital Discourse: A Critical Discourse Analysis of Al-Azhar’s Platform X - Han-Han Ulumudin Ismail (Middle Eastern Culture & Religion Issues, 2026)
This paper focuses on the analysis of the linguistics of Islamic moderation in Al-Azhar's official digital discourse in Arabic and how this construction functions as a support for the religious authority of Al-Azhar in the contemporary mediated environment. The current study adopted a qualitative design based on the socio-cognitive Critical Discourse Analysis (CDA) and Arabic micro-linguistic analysis, such that it analysed thirty tweets posted between 2019 and 2025 on Al-Azhar's verified Platform X account. The results indicate that the modulation happens through recurrent lexical patterns, nominal sentence structure (jumlah ismiyyah), masdar nominalization, definiteness marking by the prefix al-, performative institutional verb sequencing, lexical oppositions and patterned embedding of the citation of the Qur’anic text and Hadiths. There are also linguistic mechanisms which reinforce moderation as an institutional normative Islamic perspective and which highlight Al-Azhar's institutional authority in formal Arabic digital communication. The study reveals that Arabic digital religious discourse is a patterned institutional positioning that relies on grammatical form, scriptural intertextuality, and institutional register as mechanisms of authority. What is original about it is the unique combination of socio-cognitive Critical Discourse Analysis (CDA) with a close Arabic micro-grammatical analysis of the original source texts, providing a language-centred framework that brings together the fields of study on Islamic moderation, digital religion and discourse analysis.